Compactação do solo e sua influência nas propriedades físicas do solo e crescimento e rendimento de culturas - Suzuki, Luis Eduardo Akiyoshi Sanches (2005)
Sol compaction effects on soil and plants has been subject of several studies. However, several parameters are used to evaluate soil compaction like bulk density and soil penetration resistance, but these parameters are dependent of soil type and moisture, therefore, the study of a parameter that could compare the different soils would facilitate the soil compaction studies. This work was divided in four chapters. In the first chapter the objective was to evaluate some physical-mechanical parameters of Alfisols and Oxisols submitted to different tillages. Six soils from Rio Grande do Sul state, Brazil, were collected, with clay content varying from 100 to 650 g kg-1. The core samples were collected from 0.08-0.13 m layer, equilibrated to the tension of 33 kPa and submitted to uniaxial compression test with application of successive and static loads. Based on the vertical displacement measured in the consolidometer after application of each load, were evaluated initial (Dsi) and final (Dsf) bulk density, deformation (Def), initial saturation degree (Gsi), initial volumetric moisture (qvi), pre compression stress (sp) and compression index (Cc) by Casagrande s method. Results indicated that managements with larger compaction presented smaller deformation and susceptibility to compaction; managements with recent revolviment of soil presented larger displacement from their compression curves, showing larger susceptibility to compaction; the Oxisol with larger clay content, due ability to retain more water in determined tension and due larger susceptibility to compaction, need to be more careful with traffic of machines than sandy soils. The second chapter aimed to study some physical properties of Alfisols and Oxisols from Rio Grande do Sul state, Brazil, submitted to different tillages and its influence on root growth and soybean yield. R esults showed larger densities in the approximate depth of 0.10 m and the penetration resistance do not appear in layers with uniform resistance, are spaces with larger and smaller resistance; the root evaluation, even visually, it is a good indicative of the soil physical condition and the bulk density and penetration resistance, if appraised with moisture near field capacity, are good indicators of the soil for plant development; crop yield was associated to soil physical conditions. The third chapter had as objective evaluate the effect of the particles size and tillage in the degree of compactness and to verify the best pressure to obtain the reference bulk density. Six soils of Rio Grande do Sul state, Brazil, submitted to different tillages were collected, with clay content varying from 100 to 650 g kg-1. For determination of the bulk density core samples were collected from layers of 0-0.05, 0.05-0.10, 0.10-0.15, 0.15-0.20, 0.20-0.25 and 0.25-0.30 m and for evaluation of the reference bulk density core samples were collected in the layer of 0.08-0.13 m. For determination of the reference bulk density samples were equilibrated to the tension of 33 kPa and submitted to the uniaxial compression test, with application in each soil sample only one load of 200, 400, 800, 1600 kPa and 3200 kPa. It was also obtained the soil compression curve with application of successive loads in each soil sample to compare the results obtained with the samples that was applied only one load. They were evaluated also the macroporosity and soil penetration resistance, yield and root development of soybean. In agreement with the obtained results, the load of 1600 kPa was the best pressure to obtain the reference bulk density in the uniaxial compression test using core samples, independent if applying just the load of 1600 kPa or from the load of 1600 kPa of the soil compression curve; the largest soybean yield was obtained with degree of compactness of 82% for Alfisols and 85% for Oxisols and the degree of compactness was a good indicator of the physical conditions of the soil, presenting good relationship with soil penetration resistance, macroporosity, root growth and soybean yield; the degree of compactness looks like independent from particle size, based especially in the results of crop yield and macroporosity in function of degree of compactness. The fourth chapter aimed to study the effect of different compaction states on the soil physical properties and growth and yield of soybean, corn and wheat. An experiment was set in the Cooperativa Regional Tritícola Serrana Ltda (COTRIJUÍ) , Ijuí city, Rio Grande do Sul state, Brazil, in an Oxisol. The completely randomized experimental design was used, in a bifactorial with split plots, with three repetitions. The main plots had three compaction states (PDC no tillage during six years + four passes of a machine with mass of 10 Mg in the agricultural year 2003/2004; PD no tillage during six years; Escarif no tillage during six years + chisel and harrowing in the agricultural year 2003/2004) and the split plots had soybean and corn. The soil physical properties (macroporosity, microporosity, total porosity, bulk density and soil penetration resistance) and development and yield of soybean, corn and wheat were measured. The results showed that the additional compaction presented increment of the soil resistance to penetration until the depth of 0.12 m; soil compaction influenced negatively soil physical properties; soybean and wheat were sensitive to compaction, soybean and corn had reduced heights and the wheat and soybean had their root system reduced length, for the additional compaction; soil compaction affected crop yield of corn, soybean and wheat, been the larger yields verified in no tillage and the smaller in treatments with additional compaction; the larger wheat yield was observed in the succession with soybean